Using the Needham Model in Teaching Wrestling to Teach Students Some Wrestling Grips (Journal of the College of Basic Education, 2026)
Research objectives:Develop educational units based on the Needham model that are appropriate for the research sample's abilities.Identify the application of the Needham model in teaching wrestling to students to teach certain wrestling grips.The researcher used the experimental method to adapt it to the nature of the problem using the experimental design "pre-test and post-test for one group." The research sample was selected from fourth-year students in the Department of Physical Education and Sports Sciences, College of Basic Education, Al-Mustansiriya University, during the period from 10/20/2024 to 12/4/2024.The results of the tests proved the validity of the educational units used in the research, as there was a positive effect between the results of the pre- and post-tests for the experimental group, in favor of the post-tests in learning some wrestling holds. It was recommended that the educational units can be used according to the Needham model in specific small spaces and areas, especially when occupying a large area.